Geographic and temporal variations in pollen exposure across Europe. Issue 7 (10th May 2014) - Smith, M.; Jäger, S.; Berger, U.; Šikoparija, B.; Hallsdottir, M.; Sauliene, I.; Bergmann, K‐C.; Pashley, C. H.; de Weger, L.; Majkowska‐Wojciechowska, B.; Rybníček, O.; Thibaudon, M.; et al.
Abstract Background The EC‐funded EuroPrevall project examined the prevalence of food allergy across Europe. A well‐established factor in the occurrence of food allergy is primary sensitization to pollen. Objective To analyse geographic and temporal variations in pollen exposure, allowing the investigation of how these variations influence the prevalence and incidence of food allergies across Europe. Methods Airborne pollen data for two decades (1990–2009) were obtained from 13 monitoring sites located as close as possible to the EuroPrevall survey centres. Start dates, intensity and duration of Betulaceae, Oleaceae, Poaceae and Asteraceae pollen seasons were examined. Mean, slope of the regression, probability level (P) and dominant taxa (%) were calculated. Trends were considered significant at P < 0.05. Results On a European scale, Betulaceae, in particular Betula, is the most dominant pollen exposure, two folds higher than to Poaceae, and greater than five folds higher than to Oleaceae and Asteraceae. Only in Reykjavik, Madrid and Derby was Poaceae the dominant pollen, as was Oleaceae in Thessaloniki. Weed pollen (Asteraceae) was never dominant, exposure accounted for >10% of total pollen exposure only in Siauliai (Artemisia) and Legnano (Ambrosia). Consistent trends towards changing intensity or duration of exposure were not observed, possibly with the exception of (not significant) decreased exposure to Artemisia and increased exposure to Ambrosia. Conclusions This is the first comprehensive study quantifying exposure to the major allergenic pollen families Betulaceae, Oleaceae, Poaceae and Asteraceae across Europe. These data can now be used for studies into patterns of sensitization and allergy to pollen and foods.